Transcarotid artery revascularization versus transfemoral carotid artery stenting in the Society for Vascular Surgery Vascular Quality Initiative - Malas, Mahmoud B.; Dakour-Aridi, Hanaa; Wang, Grace J.; Kashyap, Vikram S.; Motaganahalli, Raghu L.; Eldrup-Jorgensen, Jens; Cronenwett, Jack L.; Schermerhorn, Marc L. (Journal of vascular surgery, 2019)
Recent evidence from the Safety and Efficacy Study for Reverse Flow Used During Carotid Artery Stenting Procedure (ROADSTER) multicenter trial in high-risk patients undergoing transcarotid artery stenting with dynamic flow reversal reported the lowest stroke rate compared with any prospective trial of carotid artery stenting. However, clinical trials have selection criteria that exclude many patients from enrollment and are highly selective of operators performing the procedures, which limit generalizability. The aim of this study was to compare in-hospital outcomes after transcarotid artery revascularization (TCAR) and transfemoral carotid artery stenting (TFCAS) as reported in the Vascular Quality Initiative (VQI). The Society for Vascular Surgery VQI TCAR Surveillance Project (TSP) was designed to evaluate the safety and effectiveness of TCAR in real-world practice. Data from the initial 646 patients enrolled in the TSP from March 2016 to December 2017 were analyzed and compared with those of patients who underwent TFCAS between 2005 and 2017. Patients with tandem, traumatic, or dissection lesions were excluded. Multivariable logistic regression and 1:1 coarsened exact matching were used to analyze neurologic adverse events (stroke and transient ischemic attacks [TIAs]) and in-hospital mortality. Patients in the two procedures were matched on age, ethnicity, coronary artery disease, congestive heart failure, prior coronary artery bypass graft or percutaneous coronary intervention, chronic kidney disease, degree of ipsilateral stenosis, American Society of Anesthesiologists class, symptomatic status, restenosis, anatomic and medical risk, and urgency of the procedure. Compared with patients undergoing TFCAS (n = 10,136), those undergoing TCAR (n = 638) were significantly older, had more cardiac comorbidities, were more likely to be asymptomatic, and were less likely to have a recurrent stenosis. The rates of in-hospital TIA/stroke as well as of TIA/stroke/death were significantly higher in TFCAS compared with TCAR (3.3% vs 1.9% [P = .04] and 3.8% vs 2.2% [P = .04], respectively). In both procedures, symptomatic patients had higher rates of TIA/stroke/death compared with asymptomatic patients (TCAR, 3.7% vs 1.4% [P = .06]; TFCAS, 5.3% vs 2.7% [P < .001]). After multivariable adjustment, there was a trend of increased stroke or death rates in TFCAS compared with TCAR, but it was not statistically significant (2.5% vs 1.7%; P = .25; odds ratio, 1.75, 95% confidence interval, 0.85-3.62). However, TFCAS was associated with twice the odds of in-hospital adverse neurologic events and TIA/stroke/death compared with TCAR (odds ratio, 2.10; 95% confidence interval, 1.08-4.08; P = .03), independent of symptom status. Coarsened exact matching showed similar results. Compared with patients undergoing TFCAS, patients undergoing TCAR had significantly more medical comorbidities but similar stroke/death rates and half the risk of in-hospital TIA/stroke/death. These results persisted despite rigorous adjustment and matching of potential confounders. This initial evaluation of the VQI TSP demonstrates the ability to rapidly monitor new devices and procedures using the VQI. Although it is preliminary, this is the first study to demonstrate the benefit of TCAR compared with TFCAS in real-world practice. These results need to be confirmed by a clinical trial. [Display omitted]